Dicyclohepta[ijkl, uvwx]rubicene with Two Pentagons and Two Heptagons as a Stable and Planar Non‐benzenoid Nanographene. Issue 9 (22nd January 2020) - Zhang, Xi‐Sha; Huang, Yan‐Ying; Zhang, Jing; Meng, Wei; Peng, Qian; Kong, Ruirui; Xiao, Zhenwei; Liu, Jie; Huang, Miaofei; Yi, Yuanping; Chen, Liangliang; Fan, Qingrui; et al.
Abstract: Polycyclic aromatic hydrocarbons with hexagons/pentagons or hexagons/heptagons have been intensively investigated in recent years, but those with simultaneous presence of hexagons, pentagons and heptagons remain rare. In this paper, we report dicyclohepta[ ijkl, uvwx ]rubicene (DHR ), a non‐benzenoid isomer of dibenzo[ bc, kl ]coronene with two pentagons and two heptagons. We developed an efficient and scalable synthetic method for DHR by using Scholl reaction and dehydrogenation. Crystal structure of DHR shows that the benzenoid rings, two pentagons and two heptagons are coplanar. The bond lengths analysis and the ICSS(1)zz and LOL‐π calculations indicate that the incorporation of two formal azulene moieties has an effect on the conjugated structure. The π‐electrons of benzenoid and pentagon rings are more delocalized. Cyclic voltammetry studies indicate that DHR shows multiple oxidation and reduction potentials. Interestingly, DHR exhibits unusual S0 to S2 absorption and abnormal anti‐Kasha S2 to S0 emission. Moreover, crystals of DHR exhibit semiconducting behaviour with hole mobility up to 0.082 cm 2 V −1 s −1 . Abstract : New nanographene : The gram‐scale synthesis of a stable and planar nanographene containing two pentagons and two heptagons is described. The material can be used as p‐type semiconductor in organic field effect transistors.